Development of the accounting treatment of dynamic coefficient of readiness of the current question at computer testing of knowledge - Тараненко, Ю.К.; Ризун, Н.О. (Eastern-European Journal of Enterprise Technologies, 2012)
The technique of an estimation of knowledge taking into account the dynamic coefficient characterizing dependence of results of testing from time is offered. The algorithm of identification of values of dynamic coefficient taking into account complexity of a question with usage of the theory of unsharp sets is developed.